PENGARUH WAKTU PENYEMPROTAN DAN KONSENTRASI PACLOBUTRAZOL (PBZ) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) VARIETAS MANADO KUNING - Bonaventura R. Lienargo; Semuel D. Runtunuwu; Johannes E.x. Rogi; Pemmy Tumewu (Universitas Sam Ratulangi, 2014)
This research was conducted at the experimental farm of the Faculty of Agriculture UNSRAT in the Pandu District Mapanget for 4 months, starting from the month Novenber 2012 to February 2013, which aims to determine the effect of spraying application time and concentration of paclobutrazol (PBZ) on the growth and yield of maize varieties Yellow Manado. The parameters measured were plant height, cob length, cob diameter, cob weight, number of rows cob, grain weight per ear. The results showed that the effect of concentration and time of application of paclobutrazol interact affect Manado Yellow corn cob weight, whereas high concentrations singly affect plants and spraying time singly affect the diameter of cob and grain weight per ear. Ear length and number of lines is not affected either concentration or time of spraying paclobutrazolKeyword: Spraying Application Time, Concentration Of Paclobutrazol (PBZ), Maize Varieties Yellow Manado